Model of Discovery learning in Science Learning: Bibliometric Analysis of the Current State of the art and Perspectives - Noor Izzati Pratiwi; Misbah Misbah; Sarah Miriam; Muhdi Harto; Nurlaela Muhammad (Journal of Mathematics Science and Computer Education, 2022)
This study aims to evaluate the most relevant themes related to discovery learning through bibliometric analysis, with its input using the keyword "Discovery learning in Science Learning". The Scopus index database is used in this study as the source database to conduct a bibliometric study for an academic article in the period between 1976 to 2022. This research also uses the VOSviewer app as a bibliometric analysis tool to visualize networks of authors, countries, journals, and keywords. This study found that the number of publications on discovery learning has grown periodically. This study also identifies the top ten authors, top ten affiliations, the top ten countries, and the top ten journal publications as sources in the field of discovery learning. Keyword analysis proves that the study of discovery learning in the last four decades has centred on themes related to computer science education, learning models, discovery learning, public understanding/outreach, high school/introductory chemistry, and constructivism. The bibliometric analysis presented in this study provides relevant information about the main theme learned about discovery learning in science learning, which is seen in the increase in creativity, learning outcomes, and student achievement in school teaching and learning activities.